2019
DOI: 10.1016/j.ijleo.2018.10.112
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of AlSi10Mg alloy fabricated by laser melting deposition and improvements via heat treatment

Abstract: Mechanical properties of AlSi10Mg alloy fabricated by laser melting deposition and improvements via heat treatment. Optik,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…The strength decreased greatly and the elongation increased significantly. In contrast to it, Lv et al (2019) found that T6 (525°C/2h 1 180°C/8h) heat treatment increased the tensile strength compared to as-built samples due to precipitation strengthening of the Mg 2 Si phase.…”
Section: Introductionmentioning
confidence: 69%
“…The strength decreased greatly and the elongation increased significantly. In contrast to it, Lv et al (2019) found that T6 (525°C/2h 1 180°C/8h) heat treatment increased the tensile strength compared to as-built samples due to precipitation strengthening of the Mg 2 Si phase.…”
Section: Introductionmentioning
confidence: 69%
“…However, no group of samples was able to excel at all tested aspects at once, indicating that parameters and strategies must be selected based on the objectives of the final results. In a broad sense, the following can be stated:  continuous pattern strategies seem to generate less denser parts, this is mainly due to the incorporation of defects such as lack of fusion/pores, associated with this strategy [66];  all samples weighted below the theoretical weight, mainly due to the inclusion of pores by a lack of fusion;  chessboard and stripes 67° pattern strategies seem to promote the best overall results, as the samples produced by these strategies are always among the best three in the tested categories;  residual stress is higher on vertical faces than horizontal faces;  the use of chessboard strategies along with build support structures generated the lowest residual stress values;  Ra surface roughness ranges between 8-12 µ m, being equivalent to certain machined surfaces (originating from sawing, drilling, milling and turning processes), casted surfaces and forged surfaces;  build orientation does not influence surface hardness; Takata, et al [79], Fiocchi, Tuissi, Bassani and Biffi [42] and Lv, et al [80] are examples of authors that have researched into the heat treatability of AlSi10Mg alloys, having observed that heat treatments in the 300 • C temperature range, or higher, lead to Si particle segregation from the supersaturated matrix in uniformly distributed manner throughout the α-Al matrix, as seen in Figure 6b, in the form a granular small particles. Also, a fading of layer and melt pool tracks begins to occur, generating a more uniform structure and mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…The HAZ area was exposed to lower temperatures, simulating a heat treatment, allowing for the formation and growth of Si particles [30,78]. Takata, et al [79], Fiocchi, Tuissi, Bassani and Biffi [42] and Lv, et al [80] are examples of authors that have researched into the heat treatability of AlSi10Mg alloys, having observed that heat treatments in the 300 °C temperature range, or higher, lead to Si particle segregation from the supersaturated matrix in uniformly distributed manner throughout the α-Al matrix, as seen in Figure 6b, in the form a granular small particles. Also, a fading of layer and melt pool tracks begins to occur, generating a more uniform structure and mechanical properties.…”
Section: Microstructurementioning
confidence: 99%
“…-17 [58] 330 [59] -7000 [60] 0.3 [59] -8.6 [61] 0.3 [57] -3 [60] 1 [ 62] -59 [63] Within range: [59][60][61][62][63][64][65][66][67] Within range: [57,58,[61][62][63][64][65][66][67] Within range: [57, 60, 62-64, 66, 67] Within range: [58,61,65] Within range: [57][58][59][60][61][62][64][65][66][67] Aluminium 6 [68] -16 [69] 120 [70] -3600 [68] 0.6 [71] -3.5 [68] 0.5 [68] 0.66 [70] -23.2 [72] Within range: …”
Section: [57]mentioning
confidence: 99%